Drying kinetics and sorption behavior of two varieties banana (sagor and sabri) of Bangladesh - Rahman, MH; Ahmed, MW; Islam, MN (SAARC Journal of Agriculture, 2019)
The study was concerned with determining the drying kinetics and sorption behavior of two varieties ripe banana of Bangladesh namely, Sagor and Sabri. The fresh ripe banana collected from the local market were sliced into three different thicknesses (4 mm, 6 mm and 8 mm) and dried at 45°C, 55°C and 65°C in a cabinet dryer. The result showed that the drying rate increases with the increase in temperature and decreases with the increase in slice thickness. The sorption properties of dried banana were studied over a wide range of water activity (0.11-0.93). The BET and GAB models were fitted to the sorption data. It was found that both varieties gave sigmoid (type II) shape isotherm and GAB equation gave the much higher value of monolayer moisture content compared to BET equation. The chemical compositions of fresh and dried banana were determined. The dried products gave substantially higher solid content as well as protein, ash and carbohydrate. SAARC J. Agri., 16(2): 181-193 (2018)